Rules of Inference and Its Application in Contemporary Transactions: In Installment Sales Model | قواعد الاستنباط وتطبيقها في المعاملات المعاصرة: في البيع بالتقسيط نموذجا - Imam Awaluddin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2015)
The islamic Jurisprudence scholars called al-ushuliyyun has reached the methods of istinbath to know the meaning of the texts of the Quran and the sunnah. The methods commanly working to understand the meaning of the text, uncovering and exposing the aims of the words in the text, and its implications. Those methods of istinbath are important to confine the disagreement among the jurists and controll its in discovering the ahkam from the texts. This article intent on presentation an importance of the methods of istinbath, and its application in contemporary issues, especially in cases of muamalat; in installment sales as the sample, by using the inductive and deductive methods. Whereas the researcher derive generally the methods of istinbath from the opinions of the islamic jurist, than apply it in installment sale, as the sample.